Sustainable Tourism: Cultural and Historical Tourism Destination, Bulang District, Batam City - Wahyu Tero Primadona (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
Batam City is one of the main tourist destinations in Indonesia, side by side with Jakarta and Bali. Various tourist destinations are available in Batam City such as shopping tourism, sports tourism, marine tourism, MICE tourism, culinary tourism, religious tourism. As an area that was once the center of civilization in the past, Bulang District is one of the administrative areas of Batam City which still maintains the original cultural identity of Batam City. The various cultures and history have the potential to be developed as a tourist destination. However, currently these various potentials have not been utilized optimally. This study used a qualitative research method with a descriptive approach. Researchers try to get a picture of the actual conditions in the field and explain it in the form of a description. Retrieval of informants using purposive sampling. The data analysis used is Miles and Huberman's interactive model. The results of the study show that Bulang District has the potential to be developed as a cultural and historical tourism destination. There is a lot of cultural and historical heritage, both Tangible Culture and Intangible Culture. The Jogi Dance from the Basri Beach Studio represents the original culture of Batam City. In addition, there are also historical relics such as the Old Forest of Pulau Buluh, Happy Shop, Jami Nurul Iman Mosque, Samudera Bhakti Temple, Temenggung Abdul Jamal Funeral Complex, Temenggung Abdul Jamal's legacy weapons such as Pauh Janggih Washing Feet, Spears, Swords, Keris, Sundang, Talam and Plates. Aspects of supporting tourism, 1) Road accessibility and communication are well available, 2) Additional facilities are minimal, 3) Additional services are limited. So it needs sustainable planning and development so that the existing potential can be utilized optimally. In addition, synergy is needed between the government and various parties.